Antibacterial Activity of Eight Medicinal Plants from the Traditional Pharmacopoeia of Niger - Mahamane Idi Issa Abdoulahi; Melogmo Dongmo Yanick Kevin; Tchokouaha Yamthe Lauve Rachel; Hama Hamadou Habibou; Bakasso Sahabi; Alio Sanda Abdelkader; Fabrice Fekam Boyom; Ilagouma Amadou Tidjani (Journal of Tropical Medicine)
The emergence of multidrug bacterial resistance poses a great public health problem and requires a constant search for new antibacterial agents. However, Niger’s flora possesses several medicinal plants used in traditional medicine to cure infectious diseases and can be used as sources of bioactive ingredients. This current study was designed to evaluate the antibacterial activity of eight plants used in the traditional pharmacopeia of Niger. The extracts were prepared by maceration using ethanol, methanol, and distilled water. The obtained extracts were screened against Salmonella spp., Shigella spp., and Escherichia coli using the microdilution method coupled with a resazurin-based assay. Phytochemical screening was performed using colorimetry, while the quantification of total polyphenols, total flavonoids, and total tannins was determined by spectrophotometry. Out of the eight plants obtained, five named Cassia italica, Limeum pterocarpum, Phyllanthus pentandrus, Strychnos innocua, and Ximenia americanum exhibited antibacterial activity with MICs ranging from 500 μg/mL to 2000 μg/mL. Phytochemical screening showed the presence of alkaloids, saponosides, tannins, flavonoids, terpenes/sterols, quinones, and polyphenols. The ethanolic and methanolic extracts of X. americana contained important quantities of total polyphenols, with 43.59 ± 0.15 and 41.97 ± 0.02 mg EAG/100 mg of extract, respectively. These extracts showed the highest contents of total tannins at 46.49 g/L and 45.52 g/L, respectively. For total flavonoids, the highest content was obtained with the methanolic extract of P. pentandrus, with 3.12 ± 0.01 mg QE/100 mg of extract. These findings justify the uses of these plants in traditional medicine for the treatment of infectious diseases such as diarrhea and can be used as starting points for the development of phytodrugs against infectious diarrhea.